A p-block metal-doped cobalt-chromium-based catalyst, a preparation method and application thereof

CN122610141BActive Publication Date: 2026-10-16NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611072959.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-16
Estimated Expiration
2046-07-20

AI Technical Summary

Technical Problem

然而,传统的制备方法如水热法、共沉淀法或常规固态烧结法,往往难以实现p区金属在钴铬尖晶石材料晶格中的均匀可控掺杂

Benefits of technology

1、本发明方法实现了p区金属的原子级均匀掺杂、强化了钴铬尖晶石材料晶体刚性并保留丰富活性位点:本发明通过“缺陷构建-分子级复合-熔盐共渗”三级协同调控策略,首先利用动态酸刻蚀在钴铬尖晶石材料表面制造缺陷位点,其不仅是活性中心,也是p区金属离子的捕获位点;继而通过湿法球磨的机械剪切力实现p区金属离子在分子水平强制锚定在缺陷位点;最后,熔盐介质提供的液相扩散环境与短时高温冲击协同作用,促使p区金属快速均匀地渗入晶格;这一过程不仅克服了传统方法中因晶格错配导致的偏析难题,又强化了钴铬尖晶石材料的晶体刚性并保留了丰富的活性位点,从而解决了掺杂不均和结构不稳定的技术瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122610141B_ABST
    Figure CN122610141B_ABST
Patent Text Reader

Abstract

The application discloses a p-region metal-doped cobalt-chromium-based catalyst and a preparation method and application thereof, and belongs to the technical field of electrocatalytic nanocatalyst preparation. The method comprises the following steps: constructing surface defects through dynamic acid etching; activating p-region metal ions by mechanical shearing force through wet ball milling and anchoring the p-region metal ions to defect sites to realize molecular-level compounding; and high-temperature short-time calcination of molten salt to promote the p-region metal to uniformly penetrate into the crystal lattice of cobalt-chromium spinel material. Through the three-level synergistic regulation strategy of "defect construction-molecular-level compounding-molten salt co-permeation", the technical problems of poor conductivity and unstable structure of the cobalt-chromium spinel material are solved synchronously, the obtained catalyst has strengthened crystal rigidity and rich active sites, and exhibits excellent oxygen evolution reaction activity, realizes long-term stable operation under industrial current density, and is suitable for alkaline water electrolysis and anion exchange membrane water electrolysis devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic nanocatalyst preparation technology, specifically relating to a p-region metal-doped cobalt-chromium-based catalyst, its preparation method, and its application. Background Technology

[0002] Among current green hydrogen production technologies, alkaline water electrolysis is relatively mature for industrial application, but it still faces bottlenecks such as low operating current density and electrolysis efficiency, high heat loss, and insufficient hydrogen purity. The emerging anion exchange membrane water electrolysis combines the advantages of non-precious metal anode catalysts in alkaline water electrolysis with the high efficiency of proton exchange membrane water electrolysis, and is considered a promising next-generation water electrolysis technology. However, because the oxygen evolution reaction at the anolyte involves a complex four-electron-proton coupling transfer process, it not only has a high thermodynamic energy barrier but also slow reaction kinetics. Therefore, designing and developing high-performance non-precious metal catalysts is crucial for the development of this technology. While cobalt-chromium spinel materials (such as CoCr2O4) possess a certain degree of structural stability, their intrinsic conductivity is poor, their active sites are insufficiently exposed, and they are prone to structural reconstruction or metal dissolution under the strong oxidizing environment of high current density in industrial applications, leading to rapid decay of catalytic performance and making it difficult to meet the stringent long-term stability requirements of industrial applications.

[0003] Existing technologies attempt to modify cobalt-chromium spinel by introducing p-block metal elements, hoping to utilize the unique electronic configuration of p-block metals to regulate the electronic structure of Co sites, optimize the adsorption energy of oxygen-containing intermediates, and thus enhance catalytic activity. However, traditional preparation methods such as hydrothermal methods, co-precipitation methods, or conventional solid-state sintering methods often fail to achieve uniform and controllable doping of p-block metals in the cobalt-chromium spinel lattice. These methods either result in insufficient doping depth due to reaction kinetic limitations or segregation of p-block metals at grain boundaries due to the lack of effective diffusion channels during high-temperature processing. This not only fails to effectively strengthen the crystal framework but may also introduce additional interfacial structures, increasing charge transport resistance. More importantly, existing technologies lack precise means to control the "crystal rigidity" of the catalyst, making it difficult to improve the material's mechanical strength to resist oxidative corrosion while maintaining sufficient lattice flexibility and surface defects to sustain high catalytic activity. This leads to an imbalance between "crystal rigidity" and "catalytic activity" in the catalyst. Summary of the Invention

[0004] This invention provides a p-region metal-doped cobalt-chromium-based catalyst, its preparation method, and its application. By utilizing a three-level synergistic control strategy of "defect construction-molecular-level composite-molten salt co-infiltration", uniform and controllable doping of p-region metal is achieved, while improving the crystal rigidity of the catalyst and retaining abundant active sites, thereby simultaneously improving the intrinsic activity and industrial-grade operational stability of the catalyst.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a p-region metal-doped cobalt-chromium-based catalyst includes the following steps: S1: The cobalt-chromium spinel material is placed in an acid solution for dynamic etching. Defect sites are constructed in situ on the material surface by gradient heating for subsequent anchoring of the p-region metal source. S2: The etched cobalt-chromium spinel material and the p-region metal source are wet ball-milled in an ethanol medium. The ethanol medium wets and disperses the material and reduces the surface energy, thereby reducing powder agglomeration and oxidation. Mechanical shearing force is used to achieve forced anchoring of p-region metal ions and defect sites, realizing molecular-level composite. After drying, the precursor composite is obtained. S3: The precursor composite is thoroughly ground and mixed with molten salt, and then subjected to short-term high-temperature calcination at 700-1000℃. The liquid-phase diffusion environment of the molten salt promotes atomic migration, and the short-term thermal shock effect promotes the uniform infiltration of p-region metal into the cobalt-chromium spinel material lattice, thereby strengthening the crystal rigidity.

[0006] In the steps described above, the acid solution in S1 is selected from at least one of sulfuric acid, hydrochloric acid, nitric acid or perchloric acid, with a pH value of 1-3; the mass-volume ratio of the cobalt-chromium spinel material to the acid solution is 300 mg: (30-60) mL.

[0007] The dynamic etching described in S1 adopts a gradient temperature method, specifically: first, etching at 30-45℃ for 1-4 hours, then increasing the temperature to 45-60℃ for 1-2 hours, and finally increasing the temperature to 60-75℃ for 0.5-1 hour.

[0008] The p-region metal source mentioned in S2 is selected from nitrates and chlorides of p-region metals, preferably at least one of aluminum nitrate, indium nitrate, gallium nitrate, bismuth nitrate, and tin tetrachloride.

[0009] The molar ratio of the etched cobalt-chromium spinel material to the p-region metal source in S2 is (8-15):1.

[0010] The wet ball milling process described in S2 has a rotation speed of 150-450 rpm / min and a time of 2-6 h.

[0011] The molten salt in S3 is selected from any one of magnesium chloride, calcium chloride, sodium chloride, and strontium chloride; the mass ratio of the precursor complex to the molten salt is 1:(1-8).

[0012] The high-temperature short-time calcination described in S3 involves a heating rate of 20-35℃ / min and a holding time of 0.5-2h. Within this timeframe, the crystal rigidity of the catalyst can be moderately enhanced. If the holding time exceeds 2h, or even reaches 6h, at high temperatures of 700-1000℃, the catalyst particles will agglomerate, reducing the exposure of active sites. Simultaneously, excessive crystallization will result in an overly regular surface structure, reducing active sites and affecting the electronic structure, thereby severely limiting catalytic activity and stability.

[0013] The present invention also provides a p-region metal-doped cobalt-chromium-based catalyst prepared by the above method, wherein the p-region metal in the catalyst is uniformly doped in the cobalt-chromium spinel lattice and has abundant surface defect states and enhanced crystal rigidity.

[0014] The present invention also provides a cobalt-chromium-based catalyst doped with the p-region metal as an anode oxygen evolution catalyst, which can be applied to alkaline water electrolysis and anion exchange membrane water electrolysis devices.

[0015] Beneficial effects: This invention provides a p-region metal-doped cobalt-chromium-based catalyst, its preparation method, and its application, which have the following advantages compared with the prior art: 1. The method of this invention achieves atomic-level uniform doping of p-region metals, strengthens the crystal rigidity of cobalt-chromium spinel materials, and retains abundant active sites: This invention adopts a three-level synergistic control strategy of "defect construction - molecular-level composite - molten salt co-infiltration". First, dynamic acid etching is used to create defect sites on the surface of cobalt-chromium spinel materials, which are not only active centers but also trapping sites for p-region metal ions. Then, the mechanical shearing force of wet ball milling is used to forcibly anchor p-region metal ions at the molecular level to the defect sites. Finally, the liquid-phase diffusion environment provided by the molten salt medium and the short-term high-temperature impact work together to promote the rapid and uniform infiltration of p-region metals into the crystal lattice. This process not only overcomes the segregation problem caused by lattice mismatch in traditional methods, but also strengthens the crystal rigidity of cobalt-chromium spinel materials and retains abundant active sites, thereby solving the technical bottlenecks of uneven doping and structural instability.

[0016] 2. This invention significantly improves the intrinsic activity and industrial-grade operational stability of the catalyst: Thanks to the above-mentioned three-stage synergistic control preparation process, the p-region metal-doped cobalt-chromium-based catalyst exhibits lower charge transport impedance, superior thermodynamic activity, and long-term operational stability, making it suitable for industrial-grade alkaline water electrolysis and anion exchange membrane water electrolysis devices; in alkaline water electrolysis devices, 500 mA cm⁻¹ -2 At the specified current density, the decay rate of the p-region metal-doped cobalt-chromium-based catalyst was only 35.11 μV h after 500 hours of continuous operation. -1 Its stability is far superior to that of the traditional hydrothermal method (174.40 μVh in Comparative Example 2). -1) and coprecipitation method (Comparative Example 3, 148.10 μV h) -1 The catalyst was prepared using [a specific method / technology]. Furthermore, in anion exchange membrane water electrolysis devices, at 500 mA cm⁻¹... -2 At the specified current density, the prepared p-region metal-doped cobalt-chromium-based catalyst showed no significant degradation after 500 hours of continuous operation. Attached Figure Description

[0017] Figure 1 X-ray diffraction patterns of the p-region metal-doped CoCr2O4 catalyst prepared in Example 1 of this invention and the pure-phase CoCr2O4 prepared in Comparative Example 1. Figure 2 The elemental mapping diagram of the p-region metal-doped CoCr2O4 catalyst prepared in Example 1 of this invention; Figure 3 The polarization curves of the oxygen evolution reaction in 1.0 M KOH medium are shown for the p-region metal-doped CoCr2O4 catalyst prepared in Example 2 of the present invention and the pure phase CoCr2O4 prepared in Comparative Example 1. Figure 4 Electrochemical impedance spectroscopy of the p-region metal-doped CoCr2O4 catalyst prepared in Example 2 of the present invention and the pure phase CoCr2O4 prepared in Comparative Example 1 in 1.0 M KOH medium. Figure 5 The chronopotential curves of the oxygen evolution reaction in 1.0 M KOH medium are shown for the p-region metal-doped CoCr2O4 catalyst prepared in Example 2 of the present invention and the pure phase CoCr2O4 prepared in Comparative Example 1. Figure 6 The p-region metal-doped CoCr2O4 catalysts prepared in Examples 3, 2, and 3 of this invention were tested in an alkaline water electrolysis device at 500 mA cm⁻¹. -2 Timing potential curves under current density; Figure 7 The p-region metal-doped CoCr2O4 catalyst prepared in Example 3 of this invention was tested in an anion exchange membrane water electrolysis device at 500 mA cm⁻¹. -2 Timing potential curve at current density. Detailed Implementation

[0018] The present invention will be further described in detail below with reference to specific embodiments and accompanying drawings: Example 1:

[0019] This embodiment provides a method for preparing a Ga-doped CoCr2O4 catalyst, specifically including the following steps: Prepare 35 mL of hydrochloric acid solution with pH=1. Weigh 300 mg of CoCr2O4 and add it to the hydrochloric acid solution. Stir magnetically for 30 min to obtain a suspension. Transfer the suspension to a round-bottom flask and perform dynamic acid etching in an oil bath by gradient heating. Etch at 35℃, 50℃, and 65℃ for 3 h, 1.5 h, and 0.8 h respectively with magnetic stirring. After centrifugation, washing, and drying, obtain the acid-etched CoCr2O4.

[0020] Weigh 1.15 mmol of the acid-etched CoCr2O4 and 0.115 mmol of Ga(NO3)3·xH2O, add ethanol, and then perform wet ball milling. The ball milling speed is 200 rpm / min, and the ball milling time is 5 h. After ball milling, the sample is dried in a vacuum drying oven at 60 ℃ to obtain the precursor complex.

[0021] Weigh 200 mg of the above precursor complex, mix it with 1.0 g of NaCl molten salt, and grind it thoroughly until homogeneous. Then transfer it to a ceramic boat and place it in a muffle furnace. Under an air atmosphere, heat it to 880 °C at a heating rate of 22 °C / min and hold it at that temperature for 1 h. After the reaction is complete, wash away the NaCl molten salt and other impurities thoroughly with ultrapure water, and dry it to obtain the Ga-doped CoCr2O4 catalyst.

[0022] Example 2:

[0023] This embodiment provides a method for preparing an In-doped CoCr2O4 catalyst, specifically including the following steps: Prepare a 45 mL hydrochloric acid solution with pH=2. Weigh 300 mg of CoCr2O4 and add it to the hydrochloric acid solution. Stir magnetically for 30 min to obtain a suspension. Transfer the suspension to a round-bottom flask and perform dynamic acid etching in an oil bath using a gradient temperature increase. Etch at 40℃, 55℃, and 70℃ for 2 h, 1 h, and 0.6 h respectively with magnetic stirring. After centrifugation, washing, and drying, obtain the acid-etched CoCr2O4.

[0024] Weigh 1.15 mmol of the acid-etched CoCr2O4 and 0.1 mmol of In(NO3)3·xH2O, add ethanol, and perform wet ball milling. The ball milling speed is 350 rpm / min and the ball milling time is 3 h. After ball milling, the sample is dried in a vacuum drying oven at 60 ℃ to obtain the precursor complex.

[0025] Weigh 200 mg of the above precursor complex, mix it with 1.4 g of SrCl2 molten salt, and grind it thoroughly until homogeneous. Then transfer it to a ceramic boat and place it in a muffle furnace. Under an air atmosphere, heat it to 900 °C at a heating rate of 25 °C / min and hold it at that temperature for 0.8 h. After the reaction is complete, wash away the SrCl2 molten salt and other impurities thoroughly with ultrapure water, and dry it to obtain the In-doped CoCr2O4 catalyst.

[0026] Example 3:

[0027] This embodiment provides a method for preparing an Al-doped CoCr2O4 catalyst, specifically including the following steps: Prepare 50 mL of sulfuric acid solution with pH=2.5. Weigh 300 mg of CoCr2O4 and add it to the sulfuric acid solution, then stir magnetically for 30 min to obtain a suspension. Transfer the suspension to a round-bottom flask and perform dynamic acid etching in an oil bath using a gradient temperature increase. Etch at 40℃, 55℃, and 75℃ for 2 h, 1 h, and 0.3 h respectively with magnetic stirring. After centrifugation, washing, and drying, obtain the acid-etched CoCr2O4.

[0028] Weigh 1.15 mmol of the acid-etched CoCr2O4 and 0.09 mmol of Al(NO3)3·9H2O, add ethanol, and then perform wet ball milling. The ball milling speed is 400 rpm / min, and the milling time is 2 h. After ball milling, the sample is dried in a vacuum drying oven at 60 °C to obtain the precursor complex.

[0029] Weigh 200 mg of the above precursor complex, mix it with 0.8 g of NaCl molten salt, and grind it thoroughly until homogeneous. Then transfer it to a ceramic boat and place it in a muffle furnace. Under air atmosphere, heat it to 840 °C at a heating rate of 30 °C / min and hold it at that temperature for 1.3 h. After the reaction is complete, wash away the NaCl molten salt and other impurities thoroughly with ultrapure water, and dry it to obtain the Al-doped CoCr2O4 catalyst.

[0030] Comparative Example 1: This comparative example provides an undoped CoCr2O4 catalyst, specifically including the following steps: Prepare a 45 mL hydrochloric acid solution with pH=2. Weigh 300 mg of CoCr2O4 and add it to the hydrochloric acid solution, then stir magnetically for 30 min to obtain a suspension. Transfer the suspension to a round-bottom flask and perform dynamic acid etching in an oil bath using a gradient temperature increase. Etch at 35℃, 50℃, and 65℃ with magnetic stirring for 3 h, 1.5 h, and 0.8 h, respectively. After centrifugation and washing, dry in a vacuum drying oven at 60℃ to obtain CoCr2O4.

[0031] Comparative Example 2: This comparative example provides an Al-doped CoCr2O4 catalyst prepared by a conventional hydrothermal method, specifically including the following steps: Weigh 1.2 mmol Co(NO3)2·6H2O, 2.4 mmol Cr(NO3)3·9H2O, 0.094 mmol Al(NO3)3·9H2O, and 11.5 mmol CO(NH2)2 and dissolve them in 35 mL of deionized water. Stir magnetically for 30 min to obtain a homogeneous solution. Transfer the solution to a 50 mL reactor and react hydrothermally at 180 °C for 4 h. After the reaction is complete, centrifuge, wash, and dry to obtain the CoCrAlLDH precursor.

[0032] The CoCrAl LDH precursor was transferred to a muffle furnace and heated to 500°C at a heating rate of 10°C / min under air atmosphere, and then calcined for 3 hours. This yielded the Al-doped CoCr2O4 catalyst.

[0033] Comparative Example 3: This comparative example provides an Al-doped CoCr2O4 catalyst prepared by a conventional co-precipitation method, specifically including the following steps: Weigh out 1.2 mmol Co(NO3)2·6H2O, 2.4 mmol Cr(NO3)3·9H2O, and 0.094 mmol Al(NO3)3·9H2O, dissolve them in 35 mL of deionized water, and stir magnetically for 30 min to obtain a homogeneous solution. While continuing stirring, add 3 M KOH solution dropwise until the metal ions are completely precipitated. Then, centrifuge, wash, and dry to obtain the precursor powder.

[0034] The precursor powder was transferred to a muffle furnace and heated to 500°C at a heating rate of 10°C / min under air atmosphere, and then calcined for 3 hours. This yielded the Al-doped CoCr2O4 catalyst.

[0035] Figure 1 X-ray diffraction patterns of the Ga-doped CoCr2O4 catalyst prepared in Example 1 and the pure-phase CoCr2O4 prepared in Comparative Example 1 are shown. As can be seen from the figures, the diffraction peak intensity of the Ga-doped CoCr2O4 catalyst is moderately enhanced compared to the pure-phase CoCr2O4, indicating that short-time high-temperature calcination treatment moderately strengthens its crystal rigidity. Furthermore, no diffraction peaks belonging to gallium or its oxides were detected, indicating that Ga is doped into the CoCr2O4 lattice.

[0036] Figure 2 The elemental mapping diagram of the Ga-doped CoCr2O4 catalyst prepared in Example 1 is shown. As can be seen from the figure, the Ga element signal is uniformly dispersed on the catalyst surface without obvious agglomeration, indicating that Ga has been uniformly doped into the CoCr2O4 lattice.

[0037] Figure 3 The polarization curves of the oxygen evolution reaction (OER) of the In-doped CoCr2O4 catalyst prepared in Example 2 and the pure-phase CoCr2O4 prepared in Comparative Example 1 are shown in 1.0 M KOH medium. As can be seen from the figure, in the three-electrode system (Hg / HgO as the reference electrode, a carbon rod as the counter electrode, and the prepared catalyst supported on glassy carbon as the working electrode), the In-doped CoCr2O4 catalyst of Example 2 exhibits superior catalytic activity, with a 10 mA cm⁻¹ activity. -2 The overpotential at current density is only 227 mV.

[0038] Figure 4 Electrochemical impedance spectroscopy (EIS) spectra of the In-doped CoCr2O4 catalyst prepared in Example 2 and the pure-phase CoCr2O4 prepared in Comparative Example 1 in 1.0 M KOH medium are shown. As can be seen from the figure, the In-doped CoCr2O4 catalyst of Example 2 exhibits a lower EIS, indicating its superior conductivity.

[0039] Figure 5 The chronopotential curves of the oxygen evolution reaction (OER) of the In-doped CoCr₂O₄ catalyst prepared in Example 2 and the pure-phase CoCr₂O₄ prepared in Comparative Example 1 in 1.0 M KOH medium are shown. As can be seen from the figure, the pure-phase CoCr₂O₄ of Comparative Example 1 exhibits a chronopotential curve of 50 mA cm⁻¹. -2 The catalyst deactivated after 100 hours of operation at the specified current density, while the In-doped CoCr2O4 catalyst in Example 2 did not show significant degradation even after more than 200 hours of operation, indicating its superior catalytic stability.

[0040] Figure 6 The Al-doped CoCr2O4 catalysts prepared in Examples 3, 2, and 3 were demonstrated to function at 500 mA cm⁻¹ in an alkaline water electrolysis device. -2 Chronopotential curves at current density. As shown in the figure, the Al-doped CoCr2O4 catalyst in Example 3 exhibits a decay rate of only 35.11 μV / h after 500 hours of operation. -1 This is far lower than that of catalysts prepared by the traditional hydrothermal method (Comparative Example 2, 174.40 μV h). -1 Catalysts prepared by conventional coprecipitation method (Comparative Example 3, 148.10 μV h) and catalysts prepared by conventional coprecipitation method -1 This demonstrates that the Al-doped CoCr2O4 catalyst prepared in Example 3 has stronger structural stability and more durable catalytic activity, making it suitable for industrial-grade alkaline water electrolysis.

[0041] Figure 7The Al-doped CoCr2O4 catalyst prepared in Example 3 was demonstrated in an anion exchange membrane water electrolysis device (device composition: nickel electrode, porous nickel gas diffusion layer, KMen anion exchange membrane, Al-doped CoCr2O4 anode catalyst, Pt / C cathode catalyst) at 500 mA cm⁻¹. -2 Chronopotential curves at current density. As shown in the figure, the catalyst showed no significant degradation even after more than 500 hours of operation, demonstrating durable catalytic activity and suitability for industrial-grade anion exchange membrane water electrolysis.

[0042] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a p-block metal-doped cobalt-chromium-based catalyst, characterized in that, Includes the following steps: S1: The cobalt-chromium spinel material is subjected to dynamic etching treatment, and defect sites are constructed in situ on the material surface through gradient heating to anchor the subsequent p-region metal source; wherein the dynamic etching treatment is carried out in an acid solution, and the mass-to-volume ratio of the cobalt-chromium spinel material to the acid solution is 300mg:(30-60)mL; the gradient heating method is as follows: first, etching is carried out at 30-45℃ for 1-4h, then the temperature is increased to 45-60℃ for 1-2h, and finally the temperature is increased to 60-75℃ for 0.5-1h. S2: The etched cobalt-chromium spinel material and the p-region metal source are mixed uniformly at a molar ratio of (8-15):

1. Mechanical shearing force is used to achieve forced anchoring of p-region metal ions and defect sites, realizing molecular-level composite and obtaining precursor composite. The mechanical shearing force is achieved by wet ball milling at a speed of 150-450 rpm / min for 2-6 hours. S3: The precursor composite is subjected to short-time high-temperature calcination using the molten salt method. The calcination temperature is 700-1000℃, the heating rate is 20-35℃ / min, and the holding time is 0.5-2h. The liquid-phase diffusion environment of the molten salt promotes atomic migration, and the short-time thermal shock effect promotes the uniform infiltration of p-region metal into the cobalt-chromium spinel material lattice, thereby strengthening the crystal rigidity.

2. The method for preparing the p-region metal-doped cobalt-chromium-based catalyst according to claim 1, characterized in that, The pH value of the acid solution is 1-3.

3. The method for preparing the p-region metal-doped cobalt-chromium-based catalyst according to claim 1, characterized in that, The p-block metal source is selected from nitrates and chlorides of p-block metals.

4. A p-block metal-doped cobalt-chromium-based catalyst, characterized in that, The catalyst is prepared by the method described in any one of claims 1-3; the p-region metal in the catalyst is uniformly doped in the cobalt-chromium spinel lattice and has surface defect states and enhanced crystal rigidity.

5. The application of the p-region metal-doped cobalt-chromium-based catalyst prepared by the method of any one of claims 1-3 or as described in claim 4, characterized in that, The catalyst is used as an anode oxygen evolution catalyst in alkaline water electrolysis or anion exchange membrane water electrolysis devices.

Citation Information

Patent Citations

  • Zinc-gallium spinel as well as preparation method and application thereof

    CN117599770A

  • Double-doped spinel catalyst as well as preparation method and application thereof

    CN122189747A